Hubungan antara Kepercayaan Diri dan Dukungan Orangtua dengan Kemandirian Belajar Siswa di SMA Dharma Pancasila Medan - Rinda Ariati Nasution; Syaiful Akhyar; Azhar Aziz (Universitas Medan Area, 2020)
The purpose of this study was to determine the relationship of self-confidence and support parents with the independence of student learning in SMA Dharma Pancasila Medan. This research is quantitative descriptive research. The population of the study were the students of SMA Dharma Pancasila Medan as many as 472 students consisting of class X as many as 4 classes, class XI as many as 5 classes, and class XII of 5 classes. By using Random Sampling Technique obtained sample of 120 respondents. The result of descriptive analysis shows that in general condition of self confidence, parent support and independence of studying high school students Dharma Pancasila classified. The results of multiple regression analysis of the first hypothesis show that there is a positive and significant relationship between self-confidence with learning independence, the contribution of 27.7%. The second hypothesis shows that there is a positive and significant correlation between parental support and learning independence, contribution of 31,2% and third hypothesis shows there is positive and significant correlation between self confidence and parent support to student learning independence with contribution equal to 41,9%. Based on the results of the study is expected all elements of the school to develop student independence through among other self-confidence planting that students can become independent individuals.